The usefulness of endoscopic ultrasound in the diagnosis of gallbladder lesions - Tamura, Takashi; Ashida, Reiko; Kitano, Masayuki (Frontiers in Medicine, 2022)
Gallbladder tumors are neoplastic lesions; however, it can be difficult to distinguish between benign and malignant gall bladder tumors before surgery, although endoscopic ultrasound (EUS) is useful for differentiation. Fundamental B mode EUS (FB-EUS) and contrast-enhanced harmonic EUS (CH-EUS) are reported to be useful for the diagnosis of gallbladder tumor because they allow evaluation of polypoid lesion and gallbladder wall thickening. Scoring systems based on FB-EUS imaging are available for the diagnosis of malignant gallbladder polypoid lesions. The characteristic findings of malignant gallbladder polypoid lesions on CH-EUS include the presence of irregular intratumoral vessels and perfusion defects. The characteristic findings of malignant gallbladder wall thickening on FB-EUS include wall thickening >12 mm, hypoechoic internal echogenicity, inhomogeneous internal echo pattern, and disrupted wall layer, whereas CH-EUS findings include hypovascular enhancement and inhomogeneous contrast distribution pattern. In addition, FB-EUS and CH-EUS are useful for evaluating the stage of gallbladder carcinoma because they allow the evaluation of the depth of invasion of the gallbladder wall. It is usually difficult to obtain pathological evidence from gallbladder tumors before surgery and chemotherapy, even though the histological diagnosis is necessary for determining treatment policy. EUS-guided fine needle aspiration (EUS-FNA) is useful for obtaining pathological samples from gallbladder tumors before surgery and chemotherapy. The accuracy rate of EUS-FNA for gallbladder tumor is as high as 90%, but complications such as bile leakage and needle track seeding can be a problem, although it was reported that contrast-enhanced harmonic imaging is useful for avoiding them.